PENERAPAN CUSTOMER RELATIONSHIP MANAGEMENT PADA SISTEM INFORMASI PEMESANAN DAN PENJUALAN PADA TOKO BUKU GAPURA BERBASIS WEB - Cosmas Tambunan; Darwis Robinson Manalu; Jimmy Febrianus Naibaho (Universitas Methodist Indonesia, 2018)
The use of technology in the application of Customer Relationship Management (CRM) becomes very important to build relationships between customers as well as providing information provided to customers. The benefits of implementing CRM are to help keep existing customers and to gain new customers. In this study the authors implement CRM in an information system E-commers on Bookstore Gapura. Where currently there is no E-commission information system available in Gapura Bookstore. The method used in this design is using Data Flow Diagram (DFD). This application is also created by using PHP programming language using MySQL. With this application so that facilitate Bookstore Gapura in providing information and promotion, so that information delivered more efficient and clear to the consumer.